U-Shaped Relationship of Rare Earth Element Lanthanum and Oral Cancer Risk: A Propensity Score-Based Study in the Southeast of China - Chen, Fa; Deng, Qingrong; Wu, Yuxuan; Wu, Yuying; Chen, Jinfa; Chen, Yujia; Lin, Lisong; Qiu, Yu; Pan, Lizhen; Zheng, Xiaoyan; Wei, Lihong; Liu, Fengqiong; et al. (Frontiers in Public Health, 2022)
As an important rare earth element (REE) extensively applied to industry, agriculture, and medicine, lanthanum (La) has attracted a host of health concerns. This study aimed to explore the relationship between La exposures and the risk of developing oral cancer through a case-control study with large sample size. Serum La levels of 430 oral cancer patients and 1,118 healthy controls were detected by inductively coupled plasma mass spectrometry (ICP-MS). The association of La level with the risk of oral cancer was assessed in two ways: 1) as a continuous scale based on restricted cubic splines (RCS); 2) as a priori defined centile categories using multivariate logistic regression model, based on propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). The RCS revealed a non-linear U-shaped relationship between serum La and oral cancer risk. Serum La deficiency or excess was associated with an increased risk for oral cancer. When La level was analyzed as a categorical variable, a similar U-shaped association was observed. Of note, compared to those with the median concentrations of La (0.243-0.341 μg/L), the risk increased with the lower or higher quantiles (0.132-0.242 μg/L vs. 0.243-0.341 μg/L: OR=1.80, 95%CI:1.07-3.02; 0.342-0.497 μg/L vs. 0.243-0.341 μg/L: OR= 2.30, 95%CI: 1.38-3.84). The results were generally consistent with PSM and IPTW analyses. This preliminary study provides strong evidence that there was a U-shaped relationship between serum La level and oral cancer risk. Much additional work is warranted to confirm our findings.